Lo extraño en la prosa de Juan Ramón Jiménez - Olivé, Laia (2024)
This article reviews and redefines the concept of the uncanny from Todorov’s theory in The Fantastic: A Structural Approach to a Literary Genre (1970) and analyses it in some barely studied prose writings by Juan Ramón Jiménez where it is present. Uncanny literature, which also lacks extensive research, is characterised by the “uncanny effect” it has on the characters and/or the reader: realizing the rarities that intermingle with our everyday life. In Jiménez’s prose, this effect manifests mainly through the compassionate way in which the narrator sees some characters who do not fit into heir environment because of their appearance and/or their behaviour. Among these, we observe children, madmen, sick people, women, foreigners, the incomprehensible and “unacquainted acquaintances”.